A Survey on Sharing Data in Cloud - Nivetha, S; Sowmya, R; Monica Jenefer, B (International Journal of Computer Sciences and Engineering, 2025)
Cloud is an online storage application mainly used to store documents, media and various files. However, due to large and easy access of cloud there arise various security issues such as data stealing and authentication issues when trying to share data on public platform. Fine-grained sharing of encrypted data is achieved through Attribute-based encryption. This is done with a methodology to provide data confidentiality and integrity using key generation, encryption and decryption. There are various techniques used to share data in cloud and each of these techniques employ different procedures or steps to achieve the end result. One among those techniques are public key encryption techniques which is a form of asymmetric key encryption where both public and private keys are used to keep the data or document secure. A security model is built through verifiable decryption algorithm. This is achieved by introducing a verification key from the output of the encryption algorithm. Finally, we present an approach to securely share data in an efficient manner through the ABE scheme.